A Critical Study of Disparities in Charity Hadith: An Isnād-cum-Matn Analysis of Sahih al-Bukhari and Sahih Muslim - Yazeed Ghinan Abdullah; Yusuf Rahman (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study investigates the wording disparity between the charity (ṣadaqah) hadiths narrated in Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, focusing on the expressions “the left hand does not know what the right hand has given” and “the right hand does not know what the left hand has given.” It aims to determine whether this textual variation affects the authenticity, transmission history, and semantic interpretation of the hadith. Theoretical framework: The research is grounded in the Isnāḍ Cum Matn (ICM) approach, which integrates transmission-chain criticism with textual analysis to reconstruct the historical development of hadith narrations and identify patterns of textual variation. Literature review: Previous studies have predominantly examined hadith authenticity through either isnād criticism or matn analysis independently. Limited scholarship has systematically combined both approaches to explain wording disparities within canonical collections, leaving the historical origins and significance of such variations insufficiently explored. Method: This qualitative study employs the Isnāḍ Cum Matn method by tracing transmission routes across pre-canonical, canonical, and post-canonical hadith collections. Comparative analysis of isnād networks and matn variants is conducted to identify the Real Common Link (RCL), evaluate transmission consistency, and examine semantic implications. Results: The analysis identifies Malik bin Anas (179H) as the Real Common Link within the transmission network. The dominant wording, “the left hand does not know what the right hand has given,” appears in multiple authoritative transmission routes, whereas the alternative wording preserved in Ṣaḥīḥ Muslim is supported by comparatively fewer narrators. The disparity therefore reflects a limited textual variation associated with specific transmission pathways rather than a contradiction or deficiency in authenticity. Both narrations remain acceptable within the broader hadith tradition. Implications: The findings reinforce the importance of integrating isnād and matn analysis to produce a more historical, contextual, and systematic understanding of hadith transmission and textual diversity. Novelty: This study demonstrates how the Isnāḍ Cum Matn approach effectively explains wording disparities within the two most authoritative Sunni hadith collections by identifying their historical transmission patterns without undermining their authenticity.